Entrelinhas com mulheres : narrativas entre clínica, mulheres e linhas - Andrade, Danielle Guss (2019)
The present work has proposed to think about the ways of constitution of women. Through writing in narratives it was possible to construct a way to compose a theoretical reference concomitant with literature and clinical practice. Authors such as Clarice Lispector, Gilles Deleuze, Felix Guattari, Stanley Keleman, Regina Favre, Michael Foucault, Suely Rolnik have been engaging in ways of aligning practice and theory. We find in these theorists concepts that corroborate with the experiences narrated in this work, such as hard lines, flexible lines, escape lines and the devir-woman.